Athletics Australia annual report 2006-07 (Annual report Athletics Australia, 2007)
HIGH PERFORMANCE PROGRAMS Our objective for high performance is to build a focused and transparent system that delivers exceptional performance outcomes in a cost effective manner by 2012. There are two core strategies for achieving high performance: 1. Establish a network of at least five event-focused National High Performance Centres (NHPCs) to provide coaches and athletes with access to the best support infrastructure within the State Institute of Sport/State Academy of Sport (SIS/SAS) framework. Some of these centres have commenced; Victoria (distance), New South Wales (sprints and relays), Australian Capital Territory (400m, 400m hurdles and jumps) and Western Australia (pole vault). 2. Create a national junior development program to identify and nurture talented young athletes. The elite junior development pathway continues in 2007 with the National Under-17 Development Squad being selected. This group will be developed by the National Youth Event Coaches (NYECs). This year we have also chosen a National Under-19 Talent Squad which will meet for two camps. Athletics International personally sponsors and supports the National Under-19 Talent Squad and provides individual mentors for each squad athlete. This is proving to be a fantastic opportunity for all. All personal coaches and mentors are invited to attend the camps with coach development and networking opportunities provided. Thirty-plus athletes will attend the World Youth Championships in Ostrava in July where they will again have the opportunity to compete against the world's best on the international stage. High performance program continued its development with refinement of the approach and development of relationships between the National Event Co-ordinators and their event coaches as well as the National Youth Event Coaches and their program.